Insurance Fraud in Russia and Abroad: Problems in Improving the Efficiency of Counteracting - P. Garmaev, Yury; N. Borovskih, Roman; P. Chumakova, Lydia; ., . (International Journal of Engineering and Technology, 2018)
The article is dedicated to the research of the insurance fraud phenomenon comparing a Russian and foreign practice of counteracting this crime. The authors, using the general scientific methods of cognition as well as the method of comparative legal analysis and other special legal methods of research, are studying the problem of counteraction the insurance fraud in Russia and other countries. The article characterizes the state of exploration of this problem from a viewpoint of Russian and foreign criminal research, analyses the criminal legislation and practice of counteracting this crime. Based on the results, the article substantiates the conclusion about a demand for a broader understanding of the insurance fraud problem and other crimes in the sphere of insurance for increasing the efficiency of combating these crimes through legal education of the population and neutralizing the false and criminogenic stereotypes of thinking of various participants in the insurance relationship.
Keywords: Comparative studies; Criminal legislation; Insurance fraud; Prevention and practice of counteraction; Russian and foreign criminal science; Scientific research.